Preliminary Study of the Cyclization of Conjugated Unsaturated Fatty Acid Chain in Kemiri Sunan Oil - Felicia Elsa; Tedi Hudaya; Tatang Hernas Soerawidjaja (Seminar Nasional Teknik Kimia Kejuangan, 2016)
The excessive usage of crude oil as the prime source of energy has caused oil deposit depletion, and therefore forced the discovery of alternative and renewable fuel resources. Through extensive studies recently, vegetable oils are believed as one of the most promising solution. Indonesia is a country with fertile land providing an ideal location for the plantation of oil-bearing plants. One of this potential is found in kemiri sunan (Reutealis trisperma) oil, which contains about 50% conjugated eleostearatic acid, which can be cyclized to form aromatic compounds. In this preliminary research, kemiri sunan oil was first saponified using KOH creating K-soap solution. Mg and Cr salts were then added to this solution in order to substitute the ion K yielding a mixture of Mg soap and Cr(OH)3 base. DEA (solvent) was added to the basic Mg soap at a 4:1 (b/b) ratio while the Cr(OH)3 acted as a catalyst for the cyclization reaction. The purpose of this research was to explore the hidden potentials in kemiri sunan to synthesize an intermediate product of an aromatic compound by varying temperature (100, 150, 200 °C) and reaction time (2, 3.5 and 5 hours). The cyclization products were tested using FTIR giving absorbance peaks at 771.53 or 779.24 cm-1 which were identified as ortho-disubsituted benzene.